Treatment of mucous membrane pemphigoid with 0.2% hyaluronic acid gel. Case Report. - Miranda-Becerril, Grace (2022)
Mucous membrane pemphigoid is a subepithelial, inflammatory, autoimmune blistering disorder that affects the body’s mucous membranes. Most of the cases appear in the oral mucosa. Corticosteroids and antimicrobials are the election treatment. This article describes the efficacy of 0.2% hyaluronic acid gel in mucous membrane pemphigoid. We report a case of a 57-year-old female patient with rheumatoid arthritis and mucous membrane pemphigoid in the upper and lower lips with three months of evolution. Lesions were treated with 0.2% hyaluronic acid gel, obtaining excellent results. The treatment of hyaluronic acid to mucous membrane pemphigoid demonstrated effectiveness in reducing inflammation, pain, and healing of the mucosa, without the need to suspend or adjust the dose of the drugs.